Does the Publishing of Short Selling Information Affect Stock Market Prices Case: Helsinki Stock Exchange - Salonen, Joona (My University, 2017)
According to the theoretical framework, the stock market can react to the public short selling information in three different ways. (1) There can be a herding reaction, (2) there can be a contrarian reaction or (3) there might be no significant reaction at all. Boehmer et al. (2010) noticed that the stock market does not adapt quickly to the public short selling information even though it should. This thesis re-examines more carefully whether the publishing of public short selling information affects stock market prices in the event date and whether it should affect the prices. The stock price development is examined on the event date and up to 50 trading days beyond event date in order to evaluate whether the public short selling information should affect stock prices. The study is conducted in the OMX Helsinki marketplace since both herding and contrarian investors exist there. Based to the academic literature, seven hypotheses are formed. The data of this study consists of two different time-series data. Firstly, the data about significant short selling positions is gathered from the online database of Finanssivalvonta. Secondly, the stock price data is gathered from the online database of Nasdaq OMX Nordic. The short position data covers all significant short positions in the Finnish stock exchange from 1.11.2012 to 31.1.2016. The data is analyzed in two phases using data processing programs Excel and SPSS. First, the event date stock price reaction is examined by comparing the event date closing price to the closing price of the previous trading day. Second, the efficiency of the event date reaction is examined by surveying the stock price development in the following 50 trading days. When re-examined more carefully, there actually were visible and significant reactions to the public short selling information. There were different kind of reactions, as both herding and contrarian reactions existed in the stock market. The reaction depended on the level of short-interest. The stocks with high short-interest faced a negative herding price reaction and the stocks with less short-interest face a positive contrarian price reaction. Both of these reactions were also efficient ones as the stock price developments continued similarly also in the following 50 trading days